Dependence of the physical properties of Sn–S film prepared by sol-gel spin-coating method on annealing temperature. (21st February 2020) - Zhai, Xiao-Na; Liu, Chao-Qian; Wang, Nan; Lun, Ting-Ting; Song, Meng-Si; Ge, Qing; Zhang, Xiao-Yang; Wu, Su-Mei; Zhao, Yu; Liu, Shi-Min; Wang, Hua-Lin; Jiang, Wei-Wei; et al.
Abstract: Sn–S films were prepared by sol-gel method and their physical properties with annealing temperature were studied. XRD analysis showed that the dominant phase in all the films was Sn2 S3 with cubic crystal structure. SEM images depicted that the flaky nanoparticles covered on the surfaces of the films except the film annealed at 500 °C. The morphology of the film annealed at 500 °C was cotton-like. The bandgaps of the films increased monotonically from 1.60 eV to 1.75 eV with the increase of annealing temperature. Moreover, the electrical properties of the films also depended on annealing temperatures.